2019
DOI: 10.36226/jrmb.v4i2.259
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Store (Mall) Environment and Money Availability Affect Consumer Impulse Buying Behavior at Surabaya City of Tomorrow Shopping Center?

Abstract: This study aims to determine the effect of store (mall) environment and money availability on consumer impulse buying in the City of Tomorrow (Cito) Surabaya. This study uses a quantitative approach whose data is obtained from the results of questionnaires. The sample in this study were 389 respondents taken based on purposive sampling technique which was included in non-probability sampling techniques. The results of this study indicate that the store (mall) environment has no effect on impulse buying. Meanwh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Thus, it revealed that more money availability are reported to have higher influence on online impulse buying behavior during COVID-19 pandemic. This result was also supported by previous research in which Hendra and Kaihatu (2019) found that money availability as the most significant factor that directly influence impulse buying behavior. In addition, consistent with the results of Pearson correlation analysis, among all factors, money availability was found to be the greatest influencing factor towards online impulse buying behavior during COVID-19 pandemic since it had the highest regression coefficient (β = 0.373).…”
Section: Respondents' Online Buying Experiencesupporting
confidence: 87%
“…Thus, it revealed that more money availability are reported to have higher influence on online impulse buying behavior during COVID-19 pandemic. This result was also supported by previous research in which Hendra and Kaihatu (2019) found that money availability as the most significant factor that directly influence impulse buying behavior. In addition, consistent with the results of Pearson correlation analysis, among all factors, money availability was found to be the greatest influencing factor towards online impulse buying behavior during COVID-19 pandemic since it had the highest regression coefficient (β = 0.373).…”
Section: Respondents' Online Buying Experiencesupporting
confidence: 87%
“…At present, there are many new-generation Internet celebrities in the Internet, and Internet celebrities make full use of self-media platforms to drive consumers' purchase behaviour through their own advantages. In recent years, internet celebrity's economy has been driven by the power of capital (Hendra and Kaihatu, 2019;Hwang and Nam, 2021;Li et al, 2021), and many internet celebrity use big data environment to carry out various promotion and marketing activities to enhance their commercial value.…”
Section: Internet Celebrity Economymentioning
confidence: 99%
“…Impulsive buying is such a vital sale-influencing phenomenon that major companies are attributing their steady sales to these factors [15]. Historically, research on impulse buying identified various antecedents such as impulse buying tendency [16], availability of time and money [17], [18], involvement [19], in-store advertising [20], instore signage [21], optimum level of stimulation [22], in-store slack [23], and displays [24].…”
Section: Literature Reviewmentioning
confidence: 99%